2005
DOI: 10.1262/jrd.17036
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses during the Peripartum Period in Dairy Cows with Postpartum Endometritis

Abstract: Abstract. Determining the immune responses to the development of endometritis during the peripartum period may assist in the development of more efficient reproductive management regimens for dairy herds. In this study, we compared the peripartum immune responses of dairy cows that develop endometritis by 4 weeks postpartum (n=11) to cows that did not develop this disease (n=19). Blood samples were collected 1 week before calving, just after or during calving, and then at weeks 1, 2, 3, and 4 postpartum. Cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 40 publications
7
46
2
9
Order By: Relevance
“…This increase in the proportion of PMN around parturition is mediated by a prepartum rise in cortisol concentrations and other hormones [42]. In the first 2 weeks after calving, the number of PMN decreases in peripheral blood because of the migration of peripheral blood PMN into the uterine lumen or mammary gland [39,43,44]. This increase of PMN in the endometrial tissue was partly confirmed in our study.…”
Section: Discussionsupporting
confidence: 78%
“…This increase in the proportion of PMN around parturition is mediated by a prepartum rise in cortisol concentrations and other hormones [42]. In the first 2 weeks after calving, the number of PMN decreases in peripheral blood because of the migration of peripheral blood PMN into the uterine lumen or mammary gland [39,43,44]. This increase of PMN in the endometrial tissue was partly confirmed in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, the significant increase of non-esterified fatty acids (NEFA) and β-Hydroxybutyrate BHBA in the serum of ketotic cows in the postparturient period confirmed the observed clinical findings. Although many studies (KEHRLI et al, 1989;GILBERT et al, 1993;MALLARD et al, 1998;KIM et al, 2005) have reported the role of the reduced functioning of neutrophils and lymphocytes in the postparturient period and the subsequent high susceptibility to infectious disease, data regarding their association with ketosis have not been completely elucidated. Therefore, the current study suggests proinflammatory cytokines and acute phase proteins as prognostic and diagnostic biomarkers of ketosis in this period.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that immunizing the cows against LKT might have reduced the detrimental effect of this toxin on intrauterine PMNs, improving the ability of the innate immune system to eliminate bacterial infections from the uterus through phagocytosis. Recruited PMNs are key players in the immune defense of the uterus; reduced migration of PMNs 2 weeks before calving is associated with retained placenta [46], and lower phagocytic activity and oxidative burst capacity of PMNs are associated with occurrence of metritis and endometritis [43], [45].…”
Section: Discussionmentioning
confidence: 99%